Perspective: Opportunities for advancing aquatic invertebrate welfare - Wahltinez, Sarah J.; Stacy, Nicole I.; Hadfield, Catherine A.; Harms, Craig A.; Lewbart, Gregory A.; Newton, Alisa L.; Nunamaker, Elizabeth A. (Frontiers in Veterinary Science, 2022)
Welfare considerations and regulations for invertebrates have lagged behind those for vertebrates, despite invertebrates comprising more than 95% of earth’s species. Humans interact with and use aquatic invertebrates for exhibition in zoos and aquaria, as pets, research subjects, and important food sources. Recent research has indicated that aquatic invertebrates, in particular cephalopod mollusks and decapod crustaceans, experience stress and may be able to feel pain. With this article, we present results of a survey on attitudes of aquatic animal health professionals toward aquatic invertebrate welfare and provide practical recommendations for advancing aquatic invertebrate welfare across four areas of opportunity: use of anesthesia, analgesia, and euthanasia; development of less invasive diagnostic and research sampling methods based on 3R principles; use of humane slaughter methods for aquatic invertebrates; and reducing impacts of invasive procedures in aquaculture and fisheries. We encourage consideration of these opportunities to achieve far-reaching improvements in aquatic invertebrate welfare.